Immigrant Memories of Healing: Textual and Pictorial Images in Erika Gottlieb’s Becoming My Mother’s Daughter - Palla, Mária (Hungarian Journal of English and American Studies, 2022)
Erika Gottlieb’s narrative is a transgenerational family memoir, a search for identity, and also the testimony of the protagonist Eva Steinbach, the thinly disguised authorial self, a child survivor of the Holocaust in Hungary, which provides a larger historical perspective for the personal narrative written in Canada. The satisfactory completion of the tasks involved in these three strands of Gottlieb’s life writing depends on how successfully memories can be preserved without allowing them to paralyze the remembering subject. Since these three themes are inseparable from each other, they can only result in self-understanding and healing for the author/protagonist if they evolve together. At the same time, Gottlieb’s narrative is intricately linked to her artwork, which calls for an intermedial discussion of the book to reveal how the graphic images further enhance the protagonist’s struggle to comprehend herself. While the multi-layered text is constructed in a non-linear structure, the sketches and paintings incorporated in it are employed to fulfill various functions. They serve both as illustrations of characters and locations at times, while on other occasions they are made to serve as structural devices. When describing or representing existing artwork, the text also turns into ekphrastic writing at certain points, thus multiplying the interpretative possibilities opened up and the aesthetic impressions created. (MP)